ON SOME ISSUES OF IMPROVING HOUSING CONDITIONS OF SERVICEMEN - Asatryan, Artak (State and Law, 2022)
Due to the start of the Nagorno-Karabakh conflict and subsequent wars, the issues related to the social rights of servicemen and their family members, military disabled persons, and military pensioners have gained great importance and have always been under the state’s care. The article discusses the issues related to improvement of the housing conditions of servicemen, as well as providing compensation for rented living space outside the place of permanent residence. In particular, the criteria on the basis of which the need to improve housing conditions at the place of service is assessed, certain categories of a serviceperson’s family members, which are taken into account when providing a serviceperson with living space or paying monetary compensation for renting living space, were discussed. In addition, in case of non-provision of an apartment to a serviceperson at the place of service, the amount of monetary compensation for renting a living space in Yerevan and the regions of the Republic of Armenia according to the composition of the family was studied. As a result of the analysis, the shortcomings, gaps and contradictions in the legal acts regulating the relations in question were highlighted, and appropriate recommendations are made for their elimination, completion and further improvement.